(untitled) (Revista de Medicina Clinica, 2022)
Atrial Septal Defects (ASDs) are one of the most common congenital heart anomalies. The patent foramen ovale (PFO) is present in 25% of the adult population and allows the passage of blood from the venous to the arterial circulation, causing a shunt. Most of the subjects will remain asymptomatic until adulthood, where after an intercurrent process, they begin to manifest the symptoms of platypnea-orthodeoxia syndrome (SPO). In relation to the COVID-19 pandemic, findings of PFO have been described after overcoming bilateral SARS-CoV-2 pneumonia, highlighting the importance of early diagnosis to avoid serious complications in this type of patient. We present two cases where the finding of PFO was incidental after having overcome respiratory infections.